Study on hot deformation behavior and dynamic recrystallization mechanism of recycled Al–Zn–Mg–Cu alloy - Chuan-guang Qin; Bo Jiang; Mao-liang Hu; Ye Wang; Hong-yu Xu; Yu Guo; Ze-sheng Ji (Journal of Materials Research and Technology, 2024)
This study utilized Al–Zn–Mg–Cu alloy chips as raw materials to prepare recycled billets through a solid-state recycling process. Isothermal hot compression tests were conducted using a thermal simulation machine to establish an Arrhenius-type constitutive equation and the hot processing map based on the dynamic materials model. The microstructure of the recycled Al–Zn–Mg–Cu alloy after hot compression was characterized and analyzed using SEM, EBSD, and TEM, exploring the microstructural evolution mechanisms of the recycled alloy at different temperatures and strain rates. The results indicate that the optimal hot deformation parameters for the recycled Al–Zn–Mg–Cu alloy are 300–360 °C at a strain rate of 0.01–0.05 s⁻1 and 400–450 °C at a strain rate of 0.05–0.3 s⁻1. At the same strain rate, as the deformation temperature increases, low-angle grain boundaries gradually disappear, and the grain structure becomes more stable. Dynamic recrystallization replaces dynamic recovery as the dominant mechanism. At the same deformation temperature, low strain rates allow more time for the migration of low-angle grain boundaries, thereby promoting the growth of dynamically recrystallized grains and ultimately forming new, undistorted grains.